INTRAOPERATIVE FLUORESCENCE DIAGNOSIS OF PERITONEAL DISSEMINATION IN PATIENTS WITH GASTRIC CANCER - E. A. Suleymanov (Biomedical Photonics, 2016)
The study of diagnostic efficiency of intraoperative ﬂuorescence diagnosis (IOFD) of peritoneal dissemination in patients with gastric cancer comparing with standard laparoscopy was performed in P.A. Hertsen MCRI (the branch of NMRRC). The study included 114 patients with veriﬁed diagnosis of gastric cancer stage III–IV. For IOFD the domestic medication alasens (the active agent – 5-aminolevulinic acid) was used orally at dose of 30 mg/kg body weight 3 h prior to the study procedure. As the result of ﬂuorescence diagnosis 10 (6.9%) patients had peritoneal tumor dissemination veriﬁed morphologically and undetected by standard laporoscopy. The sensitivity of peritoneal revision for standard laparoscopy in patients with gastric cancer stage III–IV was 60.8%, the speciﬁcity – 75.8%, the overall accuracy – 69.1%. The sensitivity for IOFD in patients with gastric cancer stage III–IV was 91.1%, the speciﬁcity – 93.9%, the overall accuracy – 92.7%. Thus, ﬂuorescence study allowed improving the speciﬁcity, the sensitivity and the overall accuracy of diagnostic test. In the trial IOFD had the maximal diagnostic value in patients with visually undetectable microdissemination in «whight» light and with solitary visible peritoneal foci (the average number of additionally detected metastatic lesions in one patient – 1.22 and 1.4, respectively). Moreover, in the case of ﬂuorescence diagnosis the number of detected microfoci of peritoneal dissemination was showed to increase with enlargement of area of tumor invasion to gastric serosa (at average of 2.29 additionally detected lesions in one patient with serosal invasion more than 2 cm2). The obtained results conﬁrm the perspective of use of ﬂuorescence diagnosis for detection of peritoneal dissemination, determination of true tumor extent, staging of the tumor and also for adjustment of following treatment tactics for this group of patients.